Designing the E-Authentic Assessment on Computer Networking Learning in The Revolution Industry 4.0 - Ambiyar, Ambiyar; Waskito, Waskito; Efendi, Raimon; Irawati, Yuyun (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The unavailability of assessment instruments that accordance to the KKNI-based higher education curriculum is also the basis of the research. This study aims at producing an online assessment evaluation model design. The type of this research was Research and Development (R&D). The research subjects were information system study program students of the Universitas Dharmas Indonesia who took the Computer Networking course. The research data were obtained through validaty and practicality instrument and also observations. Based on the research results, it can be concluded that the online authentic assessment evaluation model that has been designed can be implemented to improve learning competence. Based on descriptions and validations of each material expert, media expert, and learning expert, the resultsÂ